2018
DOI: 10.1142/s021827181850061x
|View full text |Cite
|
Sign up to set email alerts
|

Building a linear equation-of-state for trapped gravitons from finite size effects and the Schwarzschild black hole case

Abstract: In this paper we continue the investigations present in [1] and [2] concerning the spectrum of trapped gravitons in a spherical box, and in particular inside a Schwarzschild black hole (BH). We explore the possibility that, due to finite size effects, the frequency of the radiation made of trapped gravitons can be modified in such a way that a linear equation of state P V = γU for the pressure P and the internal energy U arises. Firstly, we study the case with U ∼ R, where only fluids with γ > − 1 3 are possib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(45 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…In [13,14] we have advanced a physical mechanism, mimicking solid state physics, capable, thanks to Planckian fluctuations, to change the equation of state of a radiation field into an effective one with a γ− linear equation of state. This has been firstly applied in order to explain the logarithmic corrections [13] to the semi-classical Bekenstein-Hawking entropy [15,16] and further applied in [1] in order to depict the cosmological constant. To start with, we consider the free energy F (0) (V, N, T ) of a radiation field with N excitations in a proper volume V at the temperature T and with energy E (0) in the continuum limit, given, as well known, by:…”
Section: Continuum Limit For a General Equation Of Statementioning
confidence: 99%
“…In [13,14] we have advanced a physical mechanism, mimicking solid state physics, capable, thanks to Planckian fluctuations, to change the equation of state of a radiation field into an effective one with a γ− linear equation of state. This has been firstly applied in order to explain the logarithmic corrections [13] to the semi-classical Bekenstein-Hawking entropy [15,16] and further applied in [1] in order to depict the cosmological constant. To start with, we consider the free energy F (0) (V, N, T ) of a radiation field with N excitations in a proper volume V at the temperature T and with energy E (0) in the continuum limit, given, as well known, by:…”
Section: Continuum Limit For a General Equation Of Statementioning
confidence: 99%
“…Only Planckian fluctuations can generate a cosmological constant equation of state. The physical mechanism, depicted also in [22] for a black hole and generalized in [23], is capable to transform a radiation field into one with a γ linear equation of state with p vac = γc 2 ρ vac . This can be done by considering the cosmological constant composed of massless excitations where Planckian fluctuations come into action to transform the initial radiation-like equation of state (with γ = 1/3) into a cosmological constant one (γ = −1).…”
Section: Classical Background and The Equation Of State For λmentioning
confidence: 99%
“…In any case, the physical origin of Λ, its smallness and the role of the vacuum energy in the dynamic of the universe are yet fundamental unsolved problems. Recentely, I have proposed [1,2,3,4] a way to depict the black hole entropy in terms of trapped gravitons [1,2] together with the logarithmic entropy corrections [3]. The treatment has been extended in [4] to any massless excitation.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment has been extended in [4] to any massless excitation. In particular, in [3,4] a possible mechanism transforming a radiation field into a one with a linear equation of state is presented as a theorem. In [3] it has been shown that this mechanism naturally gives, after considering quantum gravity corrections, the well known logarithmic corrections to the black hole entropy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation